2007
DOI: 10.1074/jbc.m610700200
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Response Element Organization Dictates the Composition of Active Receptor

Abstract: Thyroid hormone (triiodothyronine, T 3 ) is known to activate transcription by binding heterodimers of thyroid hormone receptors (TRs) and retinoid X receptors (RXRs). RXR-TRs bind to T 3 response elements (TREs) composed of direct repeats of the sequence AGGTCA spaced by four nucleotides (DR-4). In other TREs, however, the half-sites can be arranged as inverted palindromes and palindromes (Pal). Here we show that TR homodimers and monomers activate transcription from representative TREs with alternate half-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 57 publications
5
54
0
1
Order By: Relevance
“…DNA and/or additional transcription factors may play a role in this preselection process. DNA may also play a role in the allosteric control of coactivator binding and dimerization as suggested for TR where the binding of the SRC-1 RID is influenced by the nature of the DNA response elements (10,33). An allosteric communication between SRC-1 and DNA was reported for RXR-TR (34) and RXR-VDR (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA and/or additional transcription factors may play a role in this preselection process. DNA may also play a role in the allosteric control of coactivator binding and dimerization as suggested for TR where the binding of the SRC-1 RID is influenced by the nature of the DNA response elements (10,33). An allosteric communication between SRC-1 and DNA was reported for RXR-TR (34) and RXR-VDR (35).…”
Section: Discussionmentioning
confidence: 99%
“…RAR, like the vitamin D (VDR) and thyroid hormone (TR) receptors, heterodimerizes with rexinoid receptors (RXRs) (7). Their ability to form homodimers is also documented (8)(9)(10). RAR homodimers have been shown to be functional in yeast using a two-hybrid system, and their activity is further enhanced by the presence of SRC-2 coactivator (11).…”
mentioning
confidence: 99%
“…The primary sequence and 3D structure of TRα1 and TRβ1 are very similar, although differences are observed for key amino acids in the DNA-binding domain (9)(10)(11)(12). In most in vitro and cellular assays, they behave equally, even if TRα1 has a slightly higher affinity for T3 and is less prone to form homodimers in the absence of ligand (13). By contrast, genetic data indicate that the two receptors have very different functions in vivo.…”
mentioning
confidence: 99%
“…In other assays, however, T 4 has been found to be of lower potency than T 3 and TRIAC (5,7,8). Because various NRs, including estrogen and glucocorticoid receptors and TRs, undergo specific conformational changes upon binding to different response elements, resulting in selective recruitment of coactivator/corepressor proteins and ultimately altering the transcriptional response to a particular ligand (25,35,(46)(47)(48)(49), we wondered whether the higher relative potency of T 4 in our hands might be due to a selective stabilizing effect of the heterodimer partner RXR, the TRE, or the coactivator components on the TR-T 4 complex relative to the TR-T 3 complex.From ligand dissociation rate measurements, we found that the rapid T 4 dissociation from TR was moderated to some extent by the addition of TRE, but T 3 dissociation was unaffected. Given the fact that circulating levels of free T 4 is ~7-times higher than that of T 3 in humans (50), this suggests that T 4 might have greater effectiveness in vivo, despite its lower affinity for TR.…”
mentioning
confidence: 99%